Collaborative Strategic Reading Technique In Teaching Reading Skills - Era Rosdiana Febrianti; Usuluddin Usuluddin; Ahamd Yusri; Laila Wati (Universitas Maritim AMNI Semarang, 2023)
This study aimed at assessing the effectiveness of the Collaborative Strategic Reading (CSR) technique in enhancing reading comprehension among the eleventh-grade students at SMKN 1 Keruak during the academic year 2023-2024. A pre-experimental research design was employed, with 33 students from a single class serving as the sample. Data was collected through pre- and post-tests in the form of objective assessments, and analyzed for mean scores, standard deviation, normality, and homogeneity using SPSS 17.0 for Windows. The findings revealed that the mean score for the pre-test was 14.12, which improved to 17.18 for the post-test. The two-tailed t-test resulted in t(df=32) = -15.750 with p=0.000, indicating a significant improvement. This suggests that the Collaborative Strategic Reading technique had a noteworthy impact in enhancing reading comprehension for the eleventh graders of SMKN 1 Keruak in the academic year 2023-2024.